Oral antineoplastic agents: assessment of safety and dose adjustments in clinical practice. Issue 9 (2nd September 2019) - Escudero-Vilaplana, Vicente; Revuelta-Herrero, Jose Luis; Collado-Borrell, Roberto; Marzal-Alfaro, Belen; Gimenez-Manzorro, Alvaro; Herranz-Alonso, Ana; Sanjurjo-Saez, María
ABSTRACT: Objectives : Although the safety profile of oral antineoplastic agents (OAAs) is better than that of classic chemotherapy, the rate of severe adverse events (AEs) is high. The objective was to assess the reasons for adjustments to treatment with OAAs during the first 100 days of treatment. Methods : The authors performed a prospective observational study of cancer outpatients who initiated OAAs between November 2015 and October 2017. Dose reductions and treatment interruptions were closely followed-up during the first 100 days after the beginning of treatment with an OAA. The authors described the different safety profile of different OAA classes. Results : The authors included 443 patients (31 different OAA assessed), of whom 53.0% required their OAA to be adjusted during the first 100 days of treatment. A total of 151 patients required dose reductions and/or interruptions of OAAs owing to AEs. The authors identified 203 AEs in these patients. Treatment with sorafenib, lower ECOG performance status, and first-line treatment were associated with a higher proportion of treatment adjustments due to AEs. Conclusion : These results in clinical practice could be a first approach to help healthcare professionals to design patient monitoring programs by identifying priority patients and drugs, and remarks the importance of pharmacovigilance in OAAs.